MENINJAU KINERJA GURU ISLAM: ADVERSITY QUOTIENT DAN SPIRITUAL QUOTIENT - Tilova, Nurdinni (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Bad attitude, behavior, and low national exam scores (UN) are a reflection of the teacher's low performance. Improving fundamental aspects, such as intelligence is a good effort. This research was conducted, to review and analyze performance, by looking its determinant. The research method is quantitative with primary data. Sampling using saturated sample. The Respondents in this study are 120 teachers at Al-Madinah Islamic School Cininong Bogor. The results of the study show, Adversity Quotient has a positive and significant effect on Performance with contributions 35,8%. Spiritual Quotient has a positive and significant effect on Performance with contributions 36,5 %. Simultaneously, Adversity Quotient and Spiritual Quotient has positive and significant effect on Teacher?s Performance at Al-Madinah Islamic School Cibinong Bogor with contribution 40.4% and the residu is  59,6 % explaned by another variabel outside research